Numerical prediction of particle erosion of pipe bends (2019)
In the present study the Euler/Lagrange approach in combination with a proper turbulence model and full two-way coupling is applied for erosion estimation due to particle conveying along a horizontal to vertical pipe bend. Particle tracking considers both particle translational and rotational motion and all relevant forces such as drag, gravity/buoyancy and transverse lift due to shear and particle rotation were accounted for Laín and Sommerfeld (2012). Moreover, models for turbulent transport of the particles, collisions with rough walls and inter-particle collisions using a stochastic approach are considered Sommerfeld and Laín (2009). In this work, the different transport effects on spherical solid particle erosion in a pipe bend of a pneumatic conveying system are analysed. For describing the combined effect of cutting and deformation erosion the model of Oka et al. (2005) is used. Erosion depth was calculated for two- and four-way coupling and for mono-sized spherical glass beads as well as a size distribution of particles with the same number mean diameter (i.e. 40 μm). Additionally, particle mass loading was varied in the range from 0.3 to 1.0. The erosion model was validated on the basis of experiments by Mazumder et al. (2008) for a narrow vertical to horizontal pipe system with high conveying velocity. Then a 150 mm pipe system with 5 m horizontal pipe, pipe bend and 5 m vertical pipe with a bulk velocity of 27 m/s was considered for further analysis. As a result inter-particle collisions reduce erosion although the wall collision frequency is enhanced Sommerfeld and Laín (2015); additionally, considering a particle size distribution with the same number mean diameter as mono-sized particles yields much higher erosion depth. Finally, when particle mass loading is increased, bend erosion is reduced due to modifications of particle impact velocity and angle, although wall collision frequency grows